Environmental aspects and pavement properties of red mud waste as the replacement of mineral filler in asphalt mixture. (20th August 2018) - Zhang, Jizhe; Liu, Shengjie; Yao, Zhanyong; Wu, Shaopeng; Jiang, Hongguang; Liang, Ming; Qiao, Yaning
Highlights: Natural mineral filler was replaced by red mud to prepare asphalt mastic. Leaching toxicity and radioactivity of red mud waste were evaluated. Improved stiffness and rutting parameter of asphalt mastic indicated improved rutting resistance. The Sintering RM had the capability to improve the elastic recovery of asphalt mastic. The red mud waste can be concerned as a secondary resource to replace the natural mineral filler for asphalt pavements. Abstract: The red mud waste generated from the alumina refining industry, which remains high alkalinity and problematic pollutants, is occupying considerable land resource and causing significant environmental problems worldwide. Instead of landfills, the utilization of the red mud waste as a substitution of mineral filler in asphalt pavement mixtures has been investigated in this study. The physical and chemical properties of the red mud waste were first characterized. The experimental tests including softening point, penetration, dynamic shear rheometer (DSR) and multiple stress creep recovery (MSCR) were then conducted to evaluate the properties of asphalt mastic. Based on the results on leaching toxicity and radioactivity, the red mud waste had no risk to be used as a building material. Moreover, the addition of red mud waste can improve the stiffness and elasticity of asphalt mastic. The increased rutting parameter and the decreased accumulated creep strain were further found, especially the Sintering RM. In addition, the Sintering RM had the capability to improve the elastic recovery of asphalt mastic, while the Bayer RM had limited contribution to this behavior. Consequently, the red mud waste can be concerned as a secondary resource to replace the natural mineral filler for asphalt pavements.